Seismic and core investigation on the modern Yellow River Delta reveals the development of the uppermost fluvial deposits and the subsequent transgression system since the postglacial period. (1st October 2016) - Liu, Shihao; Li, Peiying; Feng, Aiping; Du, Jun; Gao, Wei; Xu, Yuanqin; Yu, Xiaoxiao; Li, Ping; Nan, Xueliang
Highlights: Boomer seismic profiles and boreholes were interpreted for stratigraphic structure. Structure and isopach maps were adopted to exhibit seismic structure. Several environmental proxies were measured and analyzed. We observed four units (since LGM) in both boreholes and seismic profiles. We discuss evolution pattern of the Post-LGM stratigraphy. Abstract: Postglacial stratigraphy and environmental evolution onshore and offshore the modern Yellow River Delta were investigated and analyzed through ∼1200-km high-resolution seismic profiles and four boreholes together with previous publications. Four seismic units (SU 1–4, top-to-bottom) that are bounded by seismic surfaces (T1 -T4 ) were identified in seismic profiles, while four depositional units (DU 1–4, top-to-bottom) were recognized in representative boreholes. These seismic units and depositional units exhibit good correlation. We interpreted SU 1/DU 1 as the modern Yellow River Deltaic deposits, SU 2/DU 2 as the Holocene neritic sediments, SU 3/DU 3 as a Pleistocene-Holocene transitional layer, and SU 4/DU 4 as the lowstand fluvial sediments. Apart from T1 (seafloor), T2 (deltaic base), T3 (shoreface ravinement) and T4 (transgressive surface) all dip seaward, but their dipping gradients reduced from T4 to T2 . Therefore, the thicknesses of SU 2–3 were observed seaward-thicker trends presumably in relationship with different spatial sedimentation rates. Additionally, down-core distributions of environmental proxies (e.g. grain size, microfossils and geochemical characteristics) reveal the transgression system (DU 2 and 3) can be further subdivided into 5 intervals associated with sharp environmental changes. Based on above evidences, we raised an evolutionary model of the postglacial depositional environment at the modern Yellow River Delta and adjacent marine areas, suggesting the study area evolved from riverine, estuarine, coastal, shoreface, neritic to final prodeltaic/deltaic environment since the Post-Last Glacial Maximum (LGM) in relationship with eustatic and climatic events as well as sediment input. In the model, we redefined the two-phase channel systems that exhibited in our previous study (Liu et al., 2014) as the tributaries of the LGM paleo-Yellow River and the tidal/estuarine tidal channels that formed at the early Holocene. Besides, we speculated that two hiatuses/erosions occurred at Younger Dryas and ∼4–3 cal. kyr BP, and further divided the study area into three depositional zones based on their different sedimentation rates of the transgression system.